INCIDENCE RATE OF SOME FOOD BORNE PATHOGENS BACTERIA FROM RED MEAT AND CHICKEN MEAT IN DUHOK PREVALENCE - AHMED, FATIMA SEDEEQ; ABDO, JASSIM MOHAMMED; JAKHSI, NADHIM SULAIMAN ABDULAZIZ (Journal of Duhok University, 2023)
Foods naturally provide nutrients and are easily metabolized, making them good substrates for the growth and metabolism of microbes. Food-borne illness is a widespread issue brought on by consuming tainted food and water. The bacteria that finally cause the spoiling of flesh items are either already present at the time of slaughter, or they are introduced by workers and their cutting equipment, or they are spread by water and air in the dressing, cooling, and cutting rooms.Duhok local markets, restaurant, abattoirs, contains a significant variety of imported meats and fresh meat from different sources, (minced meat, sheep meat, beef meat, chicken meat) were one of them, the current research aimed to understand an event and prevalence of bacteria in meat of meat and meat product by using biochemical in Duhok city. A total of 200 Samples of ( minced meat, sheep meat, beef meat, chicken meat), were chosen randomly from different sample of meat and meat product, all the isolates submitted to culture on many of media agar  , then the isolates tested by biochemical test to confirm final diagnosis, the study was shown there were many of bacteria reside in ( minced meat, sheep meat, beef meat, chicken meat) at a different percentage( Salmonella SPP (68%,68%,72%,56%) ,E.coli (80%,72%,68%,64%) and  Staphylococcus aureus (84%,48%,44%,72%), It could consideration meat of (minced meat, sheep meat, beef meat, chicken meat) were a viable nutrient for the growth of numerous bacteria kinds, some of which may be quite hazardous if they were to be transmitted to humans